A modification of the BCR sequential extraction procedure to investigate the potential mobility of copper and zinc in shrimp aquaculture sludge - Nemati, K.; Abu Bakar, N.K.; Sobhanzadeh, E.; Abas, M.R. (2009)
The mobility, bioavailability and persistence of copper and zinc were investigated by comparing the effect of concentration and pH changes in step 2 BCR (European Community Bureau of Reference, now known as the Standards Measurements and Testing Program) sequential extraction procedure in shrimp aquaculture farm sludge from Selangor, Malaysia. The pseudototal metal contents of shrimp aquaculture sludge samples were determined following an aqua regia digestion. The metal content in the extracts was measured by flame atomic absorption spectrometry (AAS). The concentration of Zn was increased with the increase in the concentration of hydroxylammonium chloride from 0.1 M to 0.5 M, However, further increase in the concentration of reductant caused a significant reduction in released Zn. Zinc showed the highest release percentage for hydroxylammonium chloride 0.5Â M with pH 1.5 (modified BCR sequential extraction scheme). In contrast, Cu showed the highest speciation percentage in step 2 when the unmodified sequential extraction procedure was used. Copper and zinc concentrations in this sludge, however, were not higher than the typical concentrations in soil, hence the use of this sludge as a fertilizer is suitable.